FORMATION OF FE(III) OXYHYDROXIDE COLLOIDS IN FRESHWATER AND BRACKISH SEAWATER, WITH INCORPORATION OF PHOSPHATE AND CALCIUM - Gunnars A.; Blomqvist S.; Johansson P.; Andersson C. (My University, 2002)
The formation of Fe(III) oxyhydroxide colloids by oxidation of Fe(II) and their subsequent aggregation to larger particles were studied in laboratory experiments with natural water from a freshwater lake and a brackish coastal sea. Phosphate was incorporated in the solid phase during the course of hydrolysis of iron. The resulting precipitated amorphous Fe(III) oxyhydroxide phases were of varying composition, depending primarily on the initial dissolved Fe/P molar ratio, but with little influence by salinity or concentration of calcium ions. The lower limiting Fe/P ratio found for the solid phase suggests the formation of a basic Fe(III) phosphate compound with a stoichiometric Fe/P ratio of close to two. This implies that an Fe/P stoichiometry of ~2 ultimately limits the capacity of precipitating Fe(III) to fix dissolved phosphate at oxic/anoxic boundaries in natural waters. In contrast to phosphorus, the uptake of calcium seemed to be controlled by sorption processes at the surface of the iron-rich particles formed. This uptake was more efficient in freshwater than in brackish water, suggesting that salinity restrains the uptake of calcium by newly formed Fe(III) oxyhydroxides in natural waters. Moreover, salinity enhanced the aggregation rate of the colloids formed. The suspensions were stabilised by the presence of organic matter, although this effect was less pronounced in seawater than in freshwater. Thus, in seawater of 6 to 33 %%S, the removal of particles was fast (removal half time < 200 h), whereas the colloidal suspensions formed in freshwater were stable (removal half time > 900 h). Overall, oxidation of Fe(II) and removal of Fe(III) oxyhydroxide particles were much faster in seawater than in freshwater. This more rapid turnover results in lower iron availability in coastal seawater than in freshwater, making iron more likely to become a limiting element for chemical scavenging and biologic production.